Wireless energy harvesting for sensor node applications - Liu, Alex Yingcai. (2013)
The research into wireless energy harvesting has picked up pace in the recent decades. Much progress has been made especially with the use of electromagnetic (EM) wave. Therefore the main objective of this project is to design a microstrip antenna to harvest minuscule ambient energy in the frequency range of 900 – 2.4 GHz. In this thesis, a base design is simulated and modified to increase its energy capturing capability. These design modifications are investigated in simulation and are geared towards increasing the impedance bandwidth while maintaining the other parameters as much as possible. The concept of tuning the resonant frequency is also investigated. The end results yielded 3 basic designs. The first is a single substrate dipole antenna which yielded an impedance bandwidth of 0.28GHz below -10dB with a peak return loss of approximately -39.5dB. The second is a double substrate dipole antenna that yield an impedance bandwidth of 0.302GHz below -10dB with a peak return loss of approximately -41.3dB. The final design incorporated metamaterial into the first substrate and demonstrated a greatly improved impedance bandwidth of 0.637GHz below -10dB with a peak return loss of approximately -20dB. The stimulated designs are then fabricated and the results measure to verify the simulation results.